Fighting for Memory: Poets, Readers, and Texts in Stat. theb. 12, 797-819 - Tola, Eleonora (2020)
The Thebaid´s closure programmatically displays Statius´ layered re-adaptation of the epic tradition. Ovid´s elegiac code (both erotic and exilic) and Lucan´s reshaping of Virgil´s epos place the Thebaid in a new position within the Roman literary system. Such a position results from a complex interweaving of some topoi and generic features that look back to the poet´s tradition, and simultaneously appeal to future receptions of his work. In the light of this double dynamics, I show how the association between the ideas of return and renown in the poem´s ending allows Statius to disclose an intratextual and intertextual allusive program especially focused on beginnings and endings.